A Vajdaság a Kárpát-medence történeti térszerkezetében - Csüllög, Gábor (Közép-Európai Közlemények, 2011)
It is difficult to define Voivodina –an autonomous province within the former Yugoslavia –from historical points of view, since there was no precedent of a similarly detached area of this size within the historical Hungarian state. Much the same circumstance evolved by the organization of Serbian Voivodina during the Habsburg absolutism between 1850 and 1860, but its territory formed from Backa and Banat was not exactly the same as that of the later Voivodina in Yugoslavia, partly because of military borderlands which did not belong to Serbian Voivodina and, on the other hand, because part of it was annexed to Romania by the Trianon Peace Treaty. During its two thousand-year-old history, this territory belonged to four states altogether: the Roman Empire, the Hungarian Kingdom, (within this, from the 18th century to the Hapsburg Empire), to the Ottoman Empire in the 16–17th centuries, and since 1920, to the Serbo-Croatian-Slovenian Kingdom (Yugoslavia, later Serbia). Except for the period of the Ottoman Empire, it was always situated on a given state bor-derline. Consequently, Voivodina has characteristics which essentially derive from its spatial situational and structural complications and evolve from conflicts with state territories.